A systematic review and meta-analysis of studies evaluating the performance of point-of-care tests for human papillomavirus screening. (8th December 2017) - Kelly, Helen; Mayaud, Philippe; Segondy, Michel; Pant Pai, Nitika; Peeling, Rosanna W
Abstract : Background: High-risk human papillomavirus (HPV) is a necessary cause of high-grade cervical intraepithelial neoplasia (grade 2 or higher, CIN2+). Simplified and rapid HPV DNA assays designed for use in resource-limited settings have recently become available. Methods: We performed a systematic review and meta-analysis by searching Medline, Embase, Global Health and CINAHL databases for studies from 1 January 2004 to 25 February 2017 that reported the performance of care HPV or OncoE6 for the detection of histological CIN2+ in cervical cancer screening. We used bivariate models to estimate pooled sensitivity and specificity for CIN2+ and CIN3+. Results: A total of 29 657 women were included from seven studies evaluating the performance of care HPV for the detection of CIN2+ and four studies among 27 845 women for the detection of CIN3+. The pooled prevalence for CIN2+ and CIN3+ was 2.3% and 1.1%,  respectively. care HPV had sensitivity and specificity of 88.1% (95% CI 81.4 to 92.7) and 83.7% (95% CI 74.9 to 89.8), respectively, for CIN2+ and 90.3% (95% CI 83.4 to 94.5) and 85.3% (95% CI 73.1 to 92.5), respectively, for CIN3+, using clinician-collected cervical specimen. The corresponding pooled estimates using self-collected vaginal swabs were 73.6% (95% CI 64.9 to 80.8) and 88.0% (95% CI 79.1 to 93.5) for CIN2+ and 75.2% (95% CI 66.8 to 82.0) and 90.6% (95% CI 83.4 to 94.9) for CIN3+. Two studies using OncoE6 reported sensitivity and specificity ranging from 31.3% to 42.4% and 99.1%–99.4% for CIN2+, and 53.5% and 98.9% for CIN3+ for one study. Conclusion: Care HPV has good sensitivity and specificity for the detection of CIN2+ and CIN3+, but sensitivity was lower using self-collected vaginal samples. The specificity is lower in high HPV prevalence populations such as women living with HIV. OncoE6 assay warrants further evaluation.